Tuvan and Belarusian proverbial parallels (typological community amid ethnocultural specificity) - Petrushevskaya, Julia A. (The New Research of Tuva, 2022)
One of the relevant objectives of contemporary paremiology as a separate linguistic discipline is to determine the typologically common pattern in the proverbial collections of the world’s languages amid their ethnocultural specificity due to the lack of linguistic affinity and areal proximity. An analysis of Tuvan proverbs in the typological aspect will allow to identify and measure the correlation of what is common with other languages and what is nationally specific in them. The research identifies typologically significant similarities of proverbs in the Tuvan language and reveals their ethnocultural features in comparison with proverbs in the Belarusian language. The research data comprised collections of Tuvan and Belarusian proverbs and sayings, as well as examples of proverbs from vocabulary sources of the Tuvan and Belarusian languages. It has been found out that every eighth proverb in the Tuvan proverbial fund has either a complete analog in the Belarusian one, or a Belarusian proverb that is identical in its structural and semantic model, or a homologous image and/or concept in semantically correlative proverbs in Belarusian. Such a remarkable amount and variety of interlanguage parallels of Tuvan and Belarusian proverbs indicate the typological proximity of the proverbial vocabularies of the two languages. At the same time, most of the parallels to Belarusian proverbs are nationally marked in Tuvan. This indicates a tight interrelation and interaction of typologically general and ethnoculturally specific features in the Tuvan proverbial worldview.